Nutrient supply patterns across the Sandhill Fen reclamation watershed and regional reference fens in Alberta, Canada: An ion exchange membrane study. Issue 2 (10th January 2020) - Hartsock, Jeremy A.; Bremer, Eric; Vitt, Dale H.
Abstract: Using Plant Root Simulator (PRS®) probes, we evaluate nutrient supply rates at the Sandhill Fen reclamation watershed across a gradient of increasing water table position and compare observations with three reference fens (a poor, moderate‐rich, and saline fen). Our objectives were threefold: (a) determine the behavior of PRS probes across multiple peatland classes, (b) determine which type of peatland Sandhill Fen is most analogous to in terms of nutrient supply patterns and site chemistry, and (c) attempt to provide a repeatable approach for assessing nutrient supply in peatlands. In terms of porewater chemistry, conditions at Sandhill Fen were quite unique, yet, most comparable to the saline fen. Consistent with porewater analysis, PRS probes had low nitrate supply at all sites, high calcium and magnesium supply at all sites (except the poor fen), and much higher sulfur supply at Sandhill Fen. Site differences in PRS probe measurements were smaller for 20‐ than 2‐day burial periods due to displacement of less strongly held elements (e.g., potassium) on ion exchange membranes. Because long‐term incubations may underrepresent supply rates for weakly held ions due to displacement by divalent ions, we recommend that reclamation assessments over a wide range of fen types should use a relatively short burial period of 1 to 3 days. With few exceptions (sulfate and iron), nutrient supply patterns at Sandhill Fen were quite comparable to the reference fens. For future wetland reclamation performance assessments in the AOSR, PRS probes could serve an important role for evaluating belowground functional components.